An analysis of practices, contents, and purposes of faculty meetings intended as means of improving instruction in the public secondary schools in Camarines Norte - Galvante, Gloria P. 1923-
Through this study, school administrators in the Division of Camarines Norte are provided with data on existing practices regarding faculty meetings with the aim of improving classroom instruction.